The role of interleukin 17 in the pathogenesis of rheumatoid arthritis. Are there any prospects for the use of IL-17 inhibitors? - E. L. Nasonov; A. S. Avdeeva; T. V. Korotaeva; T. V. Dubinina; Ju. V. Usacheva (Научно-практическая ревматология, 2023)
Rheumatoid arthritis (RA) is an immunoinflammatory rheumatic disease (IMRI) characterized by chronic erosive arthritis and systemic damage to internal organs, leading to early disability and reduced life expectancy in patients. Thanks to the progress in the study of the mechanisms of the development of the IVRI and industrial biotechnology, new anti-inflammatory drugs have been created, the use of which has significantly increased the effectiveness of the pharmacotherapy of RA. However, the possibilities of pharmacotherapy for RA are limited, since all biologics, regardless of the mechanism of action, have approximately the same effectiveness in achieving remission. It is believed that the relatively unsatisfactory results of RA therapy are due to the heterogeneity of the mechanisms of inflammation and pain. The significance of the Th17 type of immune response in the pathogenesis of RA, the results of controlled studies of IL-17 inhibitors, and the advisability of further studying the effectiveness of these drugs in patients with certain RA phenotypes are discussed.